Analisis Faktor – Faktor yang Mempengaruhi Pendapatan Petani Jagung di Desa Perbesi Kecamatan Tiga Binanga Kabupaten Karo - Yoshua Putra Pratama Silalahi; Khairul Saleh; Mitra Musika Lubis (Jurnal Agriuma, 2021)
The objectives of this study to determine the effect of production, land area, fertilizer costs and labor costs on the income of corn farmers in Perbesi Village, Tiga Binanga District, Karo Regency. The research was conducted using sampling techniques by purposive sampling. Prasurvey data collection as many as 427 farmers in Perbesi Village had 1-2 Ha of corn planting area so 10% of the total population was 43 farmers as samples. The results showed that simultaneously production, land area, labor costs and fertilizer costs affected the income of corn farmers in Perbesi Village, Tigabinanga District (Fcount 26.768> Ftable 2.62). Partially the production variable has significant effect (thit 2.271), land area has no significant effect –(0.868), fertilizer costs have significant effect (3.326) and labor costs (-0.875) have no significant effect on the income of corn farmers in Perbesi village, Tigabinanga district with t table 1.68959. Simultaneously all variables affect the income of corn farmers in Perbesi Village, while partially the production and cost of fertilizers have significant effect while land area and labor costs do not.